The Role of Village Development Programs and Islamic Leadership in Improving the Welfare of the Community of Pangpajung Modung Village, Bangkalan - Siti Nur Aisa; Mashudi, Mashudi; Rudi Hermawan (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the role of the Percaton Land-based village development program and the Islamic leadership of the Village Head in improving the welfare of the people of Pangpajung Village, Modung District, Bangkalan Regency. The background of this study is based on the strategic agenda of national village development that emphasizes the optimization of local resource potential through Law Number 6 of 2014 concerning Villages, in which villages are given the authority to regulate their own interests to accelerate the improvement of the quality of life of the community. The research method uses a qualitative approach with descriptive field research. Data collection techniques through in-depth interviews with the Village Head and the Percaton Land manager. The results show that the Islamic leadership of the Village Head, characterized by Islamic values ​​such as exemplary behavior, deliberation, mutual cooperation, justice, and trustworthiness, acts as a catalyst for socio-economic transformation. The Percaton Land program, managed through a profit-sharing system with intercropping patterns, effectively improves food security and the economic welfare of the community. The conclusion of this study confirms that the combination of a planned village development program with participatory, fair, and integrated Islamic leadership plays an effective role in improving the welfare of the community holistically, encompassing economic, social, and spiritual dimensions.